Implementasi Pelatihan Eco-Friendly: Konversi Minyak Jelantah Menjadi Sabun Padat pada Kelompok Masyarakat - Spalanzani, Widya; Widyantoro, Murwan; Hawani, Benita Rika; Mauliddin, Sulthan Muhammad (JICE : Journal of Industrial Community Empowerment, 2025)
Cooking oil is a widely used household commodity that generates a significant amount of waste in the form of used cooking oil. Improper disposal of this waste can lead to environmental pollution and health risks. Limited public awareness regarding these impacts remains a major challenge, particularly at the household level. This community service activity was conducted by the Industrial Engineering and Chemical Engineering study programs and targeted housewives in the Vila Gading Harapan residential area, RT 007 RW 035, Bahagia Sub-district, Bekasi Regency. The activity had two main objectives: first, to provide educational outreach on the environmental and health impacts of improper disposal and repeated use of used cooking oil; and second, to provide hands-on training on processing used cooking oil into bar soap for household use. The implementation method consisted of an educational session followed by a practical soap-making activity involving active participation from the participants. The results showed high enthusiasm among the participants and an improved understanding of environmentally friendly household waste management practices. The soap produced from used cooking oil can be utilized directly for household cleaning needs, which has the potential to reduce household expenses related to purchasing cleaning products. This activity is expected to encourage more sustainable and environmentally conscious waste management practices within the community.